Emerging infectious uveitis: Chikungunya, dengue, Zika and Ebola: A review. (2nd January 2019) - Oliver, Genevieve F.; Carr, Jillian M.; Smith, Justine R.
Abstract : Recently recognized forms of uveitis include intraocular inflammations that occur during or following one of several emerging infectious diseases: chikungunya fever, dengue, Zika virus disease and Ebola virus disease. Anterior, intermediate, posterior and pan‐uveitis have been described in individuals infected with chikungunya virus. Persons who contract dengue or Zika viruses also may develop different types of uveitis in the course of the infection: maculopathy is a common manifestation of dengue eye disease, and Zika eye disease may cause hypertensive anterior uveitis or mimic a white dot syndrome. Up to one‐third of Ebola survivors develop aggressive uveitis, which is frequently associated with vision loss and complicated by cataract. There are no specific anti‐viral drugs for these forms of uveitis, and thus treatment is largely supportive. In this article, we summarize the systemic infectious diseases and virology, and describe the clinical presentations, outcomes and management of emerging viral forms of uveitis.